Face to face : the art of human connection - Grazer, Brian, 1953- (Simon and Schuster, 2019)
In his best-seller A Curious Mind: The Secret to a Bigger Life, Academy Award-winning producer Brian Grazer helped everyone from parents to CEOs to artists to young graduates develop their curiosity into a superpower that would expand their world. Now, he reveals a new secret. Whether you're looking to develop a relationship, build your confidence, or win a negotiation, the answer is in the eyes. Grazer delves into the power of eye contact as he shares personal, life-changing stories and insightful advice that will help you immediately discover the secret to a more meaningful life. While it might seem like second nature, Grazer proves that eye contact - really looking someone in the eyes - is one of the most transformative habits you can develop in your daily life. Eye contact has the power to offer validation, show generosity, create intimacy, and - most importantly - establish genuine human connection. Even as technology takes on a bigger and bigger role in our lives, from self-driving cars to the smartphones in our pockets, no machine will ever be able to replace the unique and powerful benefits of eye contact.